(De)Construction of Queer Identities Based on the Queer Discourses in Kazakh - Ilyassov, Dulat (Nazarbayev University School of Sciences and Humanities, 2020)
This thesis examines the construction and expression of a queer identity on the example of queer fiction written in Kazakh in modern Kazakhstan. A single work of fiction titled “Renaissance”, and written by a young Kazakh man, who identifies himself as gay is analyzed in connection to the platform, on which this work is created and disseminated. The work’s connection to the notions of space and time is highlighted, in order to reveal the inner complexities of the queer experience among the Kazakh speaking gay men in Kazakhstan. The work and its sociocultural prerequisites are analyzed through the use of Foucauldian notion of heterotopia. The effect that heterotopias have on identity is studied through the use of Derridian grammatology and Deleuzian notion of rhizomatic connections. Reddit style forums on the VK social media written by and for gay men is studied with the purpose of isolating and examining various processes that are taking place within the Kazakhstani queer community. These forums are then connected to the page, on which the work of fiction under study is published. The thesis traces the metamorphoses of the main protagonist’s identity within the story. These traces are found in the language of the text, as well as the interactions between characters and the setting of the story. This analysis resulted in the understanding of queer identity as a dynamic phenomenon.
Деконструкция квир личности на основе квир дискурсов на казахском языке
Қазақ тіліндегі квир дискурстары негізіндегі квир тұлға деконструкциясы
Keywords: Derridian grammatology; rhizomatic connections; Eurasian studies; specific community